Modeling of a nanocylinder - Baranov S. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2021)
The results of the theory of modeling for obtaining nanocylinders have been described. A case of a nanocylinder whose diameters are shorter than the Tolman length has been considered. This important issue is taken into account in studying a nanocylinder for which, in the simplest model, the thickness of the interfacial layer cannot be determined because it supposedly has a small size. At the same time, it has been shown that the introduction of a special form of anisotropy energy makes it possible to analytically describe the origin of an interfacial layer whose sizes can be regarded as sizes comparable to the Tolman length.Sunt descrise rezultatele teoriei modelării pentru obținerea nanocilindrilor. Am considerat un caz în care nanocilindrul are diametre mai mici decât lungimea Tolman. Această întrebare importantă este luată în considerare atunci când se studiază nanocilindrul pentru care în cel mai simplu model nu s-a putut distinge grosimea stratului interfacial datorită dimensiunii sale presupuse mici. În același timp, se arată că introducerea unei forme speciale de energie anizotropică permite o descriere analitică a originii unui strat interfacial ale cărui dimensiuni pot fi considerate ca dimensiuni comparabile cu lungimea Tolman.